ICSH guidelines for the evaluation of blood cell analysers including those used for differential leucocyte and reticulocyte counting. (25th March 2014) - ,; Briggs, C.; Culp, N.; Davis, B.; d'Onofrio, G.; Zini, G.; Machin, S. J.; ,
Summary: This revision is intended to update the 1994 ICSH guidelines. It is based on those guidelines but is updated to include new methods, such as digital image analysis for blood cells, a flow cytometric method intended to replace the reference manual 400 cell differential, and numerous new cell indices not identified morphologically are introduced. Haematology analysers are becoming increasingly complex and with technological advancements in instrumentation with more and more quantitative parameters are being reported in the complete blood count. It is imperative therefore that before an instrument is used for testing patient samples, it must undergo an evaluation by an organization or laboratory independent of the manufacturer. The evaluation should demonstrate the performance, advantages and limitations of instruments and methods. These evaluations may be performed by an accredited haematology laboratory where the results are published in a peer‐reviewed journal and compared with the validations performed by the manufacturer. A less extensive validation/transference of the equipment or method should be performed by the local laboratory on instruments prior to reporting of results.